Micro/Bubble Drag Reduction Focused on New Applications - Adelaida García-Magariño; Pablo Lopez-Gavilan; Suthyvann Sor; Félix Terroba (Journal of Marine Science and Engineering, 2023)
Bubble drag reduction has been shown to be a promising technique for reducing the drag in ships, thus reducing the emission of pollutants and allowing the compliance with the new requirements imposed recently in this respect. Different searches have been conducted in the publications related to this technique, and an increase in interest has been shown, especially in the last decade. In this context, a review of the experimental work related to bubble drag reduction published in the last decade is presented in the present article. The works were classified according to the facility used (towing tank, cavitation tunnel, water channel, Taylor–Couette…), and the main finding are presented. It was found that two new trends in research have arisen, while there are still contradictions in the fundamental basis, which needs further study.